Legal Certainty Of Provision Of Land And Building Rights Acquisition Reduction Facilities For Foundations (Study in North Sumatra) - Panjaitan, Tulus Januardi Tua; Arifin, Muhammad; Ramlan, Ramlan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The issuance of Law Number 1 concerning Financial Relations Between the Central Government and Regional Governments has had a negative effect on foundations. Based on the results of the study, it was found that the regulation on the provision of BPHTB reduction or exemption facilities owned by foundations is an order from Law Number 28 of 2009 concerning Regional Taxes and Regional Levies, which was then followed by the issuance of Law Number 20 of 2000 concerning Amendments to Law Number 21 of 1997 concerning Land and Building Acquisition Fees. The issuance of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD) eliminates these facilities. There is a lack of synchronization in the implementation of Law Number 1 of 2002 with the regent/mayor regulations regarding the provision of BPHTB reduction or exemption facilities for foundations, considering that these regulations are still based on the old law. Law Number 7 of 2021 concerning the Harmonization of Tax Regulations is an important momentum for efforts to harmonize and synchronize taxation, including between laws and regulations and regional regulations (perda) related to taxation. Including the regulation that regulates the provision of BPHTB relief or exemption facilities for foundations. Law Number 7 of 2021 concerning the Harmonization of Tax Regulations is an important momentum for efforts to harmonize and synchronize taxation, including between laws and regulations and regional regulations (perda) related to taxation. Including the regulation that regulates the provision of BPHTB relief or exemption facilities for foundations